Impact of Chikungunya Virus on Aedes albopictus Females and Possibility of Vertical Transmission Using the Actors of the 2007 Outbreak in Italy - Bellini, Romeo (Public Library of Science, 2012)
We investigated the impact of CHIKV strains on some Aedes albopictus (Skuse) reproductive parameters and the possibility of vertical transmission. Two strains were collected in the area where the epidemic occurred in 2007, one isolated from mosquitoes, the other one isolated from a viraemic patient. Different types of blood meals, either infected or non-infected, were offered to Ae. albopictus females, that were then analyzed at increasing time post infection. The virus titre, measured by two RT-PCR methods in the blood meals, influenced the rate of infection and the rate of dissemination of CHIKV in Ae. albopictus body. We found individual variability with respect to the infection/dissemination rates and their latency both considering the female's body and appendages. The hatching rate was significantly lower for the eggs laid by the infected females than for the control eggs, while the mortality during the larval development (from first instar larva to adult emergence) was similar among the progeny of infected and non-infected female groups. Our findings seem to support the hypothesis that the vertical transmission is a rare event under our conditions, and that a certain time period is required in order to get the ovarioles infected. Field observations conducted during the Spring 2008 showed no evidence of the presence of infected overwintering progeny produced by Ae. albopictus females infected during the 2007 outbreak.